Strategic information systems : concepts, methodologies, tools, and applications - Hunter, M. Gordon (Information Science Reference, 2010)
"This 4-volume set provides a compendium of comprehensive advanced research articles written by an international collaboration of experts involved with the strategic use of information systems"--Provided by publisher
Keywords: Betriebliches Informationssystem; Information technology -- Management; Informationsmanagement; Management information systems; Programmierung; Strategic planning; Strategisches Management; Theorie